2017
DOI: 10.1038/nature23899
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium isotope evidence that accretional vapour loss shapes planetary compositions

Abstract: It has long been recognised that Earth and other differentiated planetary bodies are chemically fractionated compared to primitive, chondritic meteorites and by inference the primordial disk from which they formed. An important question has been whether the notable volatile depletions of planetary bodies are a consequence of accretion1, or inherited from prior nebular fractionation2. The isotopic compositions of the main constituents of planetary bodies can contribute to this debate3–6. Using a new analytical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
130
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(145 citation statements)
references
References 68 publications
(96 reference statements)
12
130
3
Order By: Relevance
“…The δ 26 Mg values of a seawater reference material (NASS‐6) and two rock reference materials (AGV‐2 and BHVO‐2) were also determined. The results (Table ) are in good agreement with the previous published values …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The δ 26 Mg values of a seawater reference material (NASS‐6) and two rock reference materials (AGV‐2 and BHVO‐2) were also determined. The results (Table ) are in good agreement with the previous published values …”
Section: Resultssupporting
confidence: 92%
“…employed to provide ubiquitous traceability in the fields of geochemistry, speleology, hydrology, oceanography, paleoclimatology, cosmochemistry, and biology, [3][4][5][6][7][8][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] such as understanding biogeochemical processes, 6,14,17,28 tracing fluid/melt-mineral interaction, 29 characterizing chemical weathering, 5,11,12 exploring earth and planetary evolution, 3,4,13 and reconstructing climate history. 5,15,16 To date, a range of~6‰ in the 26 Mg/ 24 Mg ratios has been observed in various types of natural samples.…”
mentioning
confidence: 99%
“…Young et al (2009) found that the BSE has higher 25 Mg/ 24 Mg than chondrites. This early claim has been refined significantly by higher-precision measurements by Hin et al (2017) (Figure 1, left panel). This latest work suggests that Earth, Mars, Vesta (HED meteorites), and the angrite parent body are all high in 25 Mg/ 24 Mg relative to chondrites (Figure 1) and the authors attribute this effect to evaporative losses from magma produced by collisions.…”
Section: Introductionmentioning
confidence: 87%
“…Because of the difficulties of losing vapor from planet-sized bodies due to their strong gravity, attention has focused on volatile losses from smaller bodies on their way to forming planets. Possible candidates include planetesimals with radii up to ~1,000 km that may have grown with the assistance of gas in the protostellar disk leading to rapid formation timescales (Levison et al Mg/ 24 Mg and 29 Si/ 28 Si for various solar system rocky bodies (Pringle et al 2013;Savage and Moynier 2013;Zambardi et al 2013;Hin et al 2017) represented here as probability density plots. Both isotope ratios are shown as per mil deviations from the standard DSM-3 and NBS-28 materials for Mg and Si, respectively.…”
Section: Planetesimal Magma Oceansmentioning
confidence: 99%
“…In contrast, Li is the least volatile element among MVEs (e.g., Sossi and Fegley, 2018) and there is no measurable difference between CCs and OCs in Li isotopes (Pogge von Strandmann et al, 2011). Similarly, for the mass-dependent isotope systems of non-volatile elements (50 % condensation temperatures higher than Li), CCs and OCs also show no resolvable difference, such as Mg (e.g., Teng et al, 2010;Schiller et al, 2010;Bourdon et al, 2010;Pogge von Strandmann et al, 2011;Hin et al, 2017), Si (e.g., Georg et al, 2007;Fitoussi et al, 2009;Armytage et al, 2011;Dauphas et al, 2015), Ca (e.g., Simon and DePaolo, 2010;Valdes et al, 2014;Huang and Jacobsen, 2017), Ti (e.g., Greber et al, 2017;Deng et al, 2018), V (e.g., Nielsen et al, 2014;Xue et al, 2018), and Fe (e.g., Craddock and Dauphas 2011;Poitrasson et al 2004;Wang et al 2013). The fact that only isotopes of elements more volatile than Li (e.g., K, Cu, Zn and Rb) show a mass dependent dichotomy between the CCs and OCs is still intriguing.…”
Section: The K Isotope Comparison Between Carbonaceous Ordinary and mentioning
confidence: 99%